MAKING RESEARCH VALUABLE: APPLYING PICOT AND POEM TO CLINICAL RESEARCH - Tuan, Nguyen (Journal of Health and Aging, 2025)
Formulating a clear and structured research question is a critical first step for the success of a medical study. However, many clinicians struggle with this initial phase, leading to unfocused research with little potential for significant impact on practice. In this paper, I introduce the PICOT framework, which can transform vague curiosities into precise, answerable questions suitable for practical research methodologies.However, a well-structured question is insufficient if it does not lead to outcomes that are meaningful to patients. The POEM (Patient-Oriented Evidence that Matters) principle provides a filter for evaluating research questions, ensuring that studies focus on outcomes relevant to patient health, rather than solely on biochemical markers. PICOT and POEM are two core principles of evidence-based medicine that help clinicians prioritize research that will positively change clinical practice and directly benefit patients. This ensures that time and resources are invested in research that generates evidence truly applicable at the bedside.
Keywords: Evidence-Based Medicine; PICOT framework; POEM framework